Editorial: post‐operative elevation of liver enzymes and modern volatile anaesthetics—guilty as charged?. Issue 9 (12th April 2019) - Laschtowitz, Alena; Sebode, Marcial
Abstract : Linked Content This article is linked to Bishop et al and Nicoll et al papers. To view these articles, visit https://doi.org/10.1111/apt.15168 and https://doi.org/10.1111/apt.15237 .